Controlled synthesis of low-molecular-weight polyethylene waxes by titanium-biphenolate-ethylaluminum sesquichloride based catalyst systems - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Applied Polymer Science, 2007)
Soluble complexes of titanium(IV) bearing sterically hindered biphenols, such as biphenol, 1,1'-methylene di-2-naphthol, 2,2'-methylene bis(4-chlorophenol), 2,2'-methylene bis(6-tert-butyl-4-ethyl phenol), and 2,2' ethylidene bis(4,6-di-tert-butyl phenol), were prepared and characterized. These catalyst precursors, formulated as [Ti((OO)-O-boolean AND)X-2], were active in the polymerization of ethylene at high temperatures in combination with ethylaluminum sesquichloride as a cocatalyst. The ultra-low-molecular-weight polyethylenes (PEs) were linear and crystalline and displayed narrow polydispersities. The catalytic polymerization leading to PE waxes in this reaction exhibited unique properties that have potential applications in surface coatings and adhesive formulations. (c) 2007 Wiley Periodicals, Inc.
Keywords: Catalysts; polyethylene (PE); synthesis; Ziegler-Natta polymerization

Polyethylene waxes: catalytic synthesis by ti-biphenolates - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Macromolecular Science Part A‐Pure and Applied Chemistry, 2007)
{Soluble complexes of Ti (IV) bearing biphenol groups such as 1,1'-binaphthelene 2, 2' diol (Binol), 1, 1'-methylene di-2-naphthol, biphenol were prepared and characterized. These catalyst precursors formulated as [
Keywords: fibers; Nanoparticles; Self-assembly